Advances in Unsaturated Geotechnics 2000
DOI: 10.1061/40510(287)7
|View full text |Cite
|
Sign up to set email alerts
|

Soil–Water Characteristic Curve Variability

Abstract: Effect of wetting-drying cycles on a residual amphibolite soil's suction from western Medellin in a natural and compacted stateSlope stability is affected by a variety of physical and chemical phenomena, climate is one of the most relevant factors in this regard. In tropical areas there are great meteorological variations throughout the year, and surface soils are the most susceptible to changes in humidity and temperature that affect their behavior and resistance.To evaluate the influence of these variations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 43 publications
3
85
0
4
Order By: Relevance
“…Among the numerous empirical equations that can formulate the SWCCs, Fredlund and Xing's (1994) sigmoidal model has been widely used and validated for large ranges of soil types and suction values (Zapata et al, 2000). The model is expressed as: …”
Section: Fredlund and Xing Swcc Modelmentioning
confidence: 99%
“…Among the numerous empirical equations that can formulate the SWCCs, Fredlund and Xing's (1994) sigmoidal model has been widely used and validated for large ranges of soil types and suction values (Zapata et al, 2000). The model is expressed as: …”
Section: Fredlund and Xing Swcc Modelmentioning
confidence: 99%
“…The soil water characteristic curve used in this analysis is based on a relationship suggested by Zapata et al 32 A family of curves for different w 3 PI is shown in Fig. 13, where w is the fraction of soil passing sieve #200 (75 ìm) as an index between 0 to 1, and PI is the plasticity index.…”
Section: Initial Evaluation Of Numerical Modelmentioning
confidence: 99%
“…The calculated a, n parameters were correlated with soil index properties, and especially the weighted PI. Weighted PI (Zapata et al 2000) is defined as the product of the material passing the #200 U.S. Standard Sieve expressed as a decimal with the Plasticity Index expressed as a percentage. It was found that the a of the Brutsaert model or 1/a of the Burdine and Mualem models can be fairly described as a logarithmic expression of wPI.…”
Section: Simulation Results and Correlationsmentioning
confidence: 99%